Prospects of a fruit lover in the "short grass" country - Greene, George Ogden (My University, 1900)
Introduction: When we look at our broad prairies, with their grazing cattle, our waving wheat fields, with the buzz of the many harvesters, we think the people should be happy; as they are, in a way. But when we look at the six-by-ten garden, full of weeds and empty tin-cans, we wonder why people do not spend less time in raising wheat and cattle and more time in living. Anywhere in Western Kansas, you may see a farm house, fit for a city dwelling, standing alone on the prairie, with the wheat-field coming to the door-step, and not a tree or a shrub in sight, not even a plum bush to shade the hungry hound or furnish fruit for a few astringent pies for the owner, who takes his fruit in the shape of wormy dried apples or spoiled canned tomatoes, shipped from the factories during the ice age. It is our purpose in this paper to show how a few of the evils of tin poisoning and everlasting fruit hunger may be overcome.
Citation: Greene, George Ogden. Prospects of a fruit lover in the "short grass" country. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Horticulture; Fruit; Cultivation;; Theses